Transformation of the Pemuda Pancasila Organization into a Formal Political Force in North Sumatra - Shah, El Adrian; Kusmanto, Heri; Situmorang, Tonny (Universitas Medan Area, 2025)
This article or writing aims to understand the process and factors that affect the change of the PP's image, increase legitimacy, and increase public acceptance of this organization after engaging in practical politics. This study uses a qualitative method with a case study approach through in-depth interviews with senior PP cadres and figures and analysis of organizational documents and related policies. The Resource Mobilization Theory is used to analyze the strategies and resources of the PP in the transformation process. At the same time, the Political Opportunity Structure helps to understand the PP's use of post-reform political opportunities in achieving formal political positions. This study concludes that the results show that PP adopts strategies such as participation in social activities, internal reforms, and strengthening political alliances to improve its image. Although the stigma of thuggery remains, the involvement of PP in social programs is beginning to increase public acceptance. Political and economic motivation is the main driver for PP cadres to enter formal politics, supported by an adaptive organizational structure.